Testosterone replacement therapy for older men - Stephen E Borst (Dove Medical Press, 2008)
Stephen E Borst, Thomas MulliganGeriatrics Research, Education, and Clinical Center, North Florida/South Georgia Veterans Health System, Gainesville, FL, USAAbstract: Despite intensive research on testosterone therapy for older men, important questions remain unanswered. The evidence clearly indicates that many older men display a partial androgen deficiency. In older men, low circulating testosterone is correlated with low muscle strength, with high adiposity, with insulin resistance and with poor cognitive performance. Testosterone replacement in older men has produced benefits, but not consistently so. The inconsistency may arise from differences in the dose and duration of testosterone treatment, as well as selection of the target population. Generally, studies reporting anabolic responses to testosterone have employed higher doses of testosterone for longer treatment periods and have targeted older men whose baseline circulating bioavailable testosterone levels were low. Most studies of testosterone replacement have reported anabolic that are modest compared to what can be achieved with resistance exercise training. However, several strategies currently under evaluation have the potential to produce greater anabolic effects and to do so in a safe manner. At this time, testosterone therapy can not be recommended for the general population of older men. Older men who are hypogonadal are at greater risk for the catabolic effects associated with a number of acute and chronic medical conditions. Future research is likely to reveal benefits of testosterone therapy for some of these special populations. Testosterone therapy produces a number of adverse effects, including worsening of sleep apnea, gynecomastia, polycythemia and elevation of PSA. Efficacy and adverse effects should be assessed frequently throughout the course of therapy.Keywords: aging, testosterone, hypogonadism, physical function